Ernst Bloch and the Spirituality of Utopia. Issue 3 (1st October 2016) - Thompson, Peter
Abstract : This essay outlines the significance of the unknowable and the spiritual in the works of Ernst Bloch. Bloch argued that Marxism needed to generate a "warm stream" of analysis to complement the "cold stream" of socioeconomic categories. His major works, The Principle of Hope and The Spirit of Utopia, represent attempts to provide this warm stream. This means that he was one of the few Marxist thinkers who took religion and faith seriously and attempted to find within them and within communism a common root of the anticipatory consciousness of a different world. His central operator was the Not-Yet, meaning that the tendencies latent in human development cannot be fully realized under current conditions. It is therefore spirit that carries these latent tendencies.